DIAMETER STRUCTURE AND PHYTOSOCIOLOGICAL FREQUENCY OF A “TERRA FIRME” AMAZON FOREST, BEFORE AND AFTER SELECTIVE CUTTING - da Cunha, Ulisses Silva; Machado, Sebastião do Amaral; Filho, Afonso Figueiredo; de Freitas, Joberto Veloso (Floresta, 2012)
This article aims to characterize horizontal and diameter structure of a managed forest using graphic expression techniques. Data for this research is result of complete forest inventory (census) carried out from a block of 800 hectares, before and after selective cutting, inside Tapajós National Forest, located in the Municipality of Belterra, State of Pará, Brazil. The analysis revealed that, in relation to horizontal structure, intense cutting resulted in changes of different levels mainly to phytosociological frequency of some species, such as, Manilkara huberi, Carapa guianensis and Tabebuia serratifolia. The diameter structure of some species, such as Sextonia rubra and Dipteryx odorata, revealed changes after selective cutting under technically acceptable rates, because the stock levels of some diameter classes surpassed the limits of balance observed for polycyclic systems with silviculture based on natural regeneration. The inclusion of graphics in the harvest operating plan for the 10 most important species listed in forest management, that is, before and after selective cutting, would lead to the desirable structure maintenance. Keywords: Diameter distribution; cutting cycle; forest management; Amazonian forest; graphic techniques. Resumo Estrutura diamétrica e frequência fitossociológica de uma Floresta de Terra Firme da Amazônia brasileira antes e depois do corte seletivo. O objetivo da presente pesquisa foi caracterizar a estrutura horizontal e diamétrica de uma floresta manejada usando técnicas de expressão gráfica. Os dados provieram de um inventário florestal sob completa enumeração (censo) efetuado em um bloco de 800 hectares, antes e depois de um corte seletivo dentro da Floresta Nacional do Tapajós, localizada no município de Belterra, Pará. As análises mostraram que a intensidade de corte utilizada promoveu diferentes níveis de alteração na estrutura horizontal, com mudanças mais significantes nas taxas de frequência fitossociológica de algumas espécies, tais como Manilkara huberi, Carapa guianensis e Tabebuia serratifolia. A estrutura diamétrica de algumas espécies, tais como Sextonia rubra e Dipterix odorata, apresentou alterações após o corte seletivo acima de taxas tecnicamente aceitáveis, porque o nível de estoque de algumas classes de diâmetro ultrapassou limites de balanço observado para sistemas policíclicos com silvicultura baseada na regeneração natural. A inclusão de gráficos no plano de operação de colheita para as 10 espécies mais importantes listadas no manejo, isto é, antes e depois do corte seletivo, induziria à estrutura desejada a ser mantida. <span style="font-size: 9.0pt; line-height: 150%; font-family: 'Times New Roman','serif'; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: PT-BR; mso-fareast-language: PT-BR; mso-bidi-language: AR-SA;">Palavras-chave:<span style="font-size: 9.0pt; line-height: 150%; font-family: 'Times New Roman','serif'; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: PT-BR; mso-fareast-language: PT-BR; mso-bidi-language: AR-SA;"> Distribuição de diâmetro; ciclo de corte; manejo florestal; Floresta Amazônica; técnicas gráficas.